Synthetic studies toward tricyclic cembranoids: a modular approach for the construction of the tricyclic framework of eunicin - Gurjar, MK; Nayak, S; Ramana, CV (Tetrahedron Letters, 2005)
The synthesis of a sugar derived allene and its intramolecular silver mediated etherification followed by ring closing metathesis has been explored for building the tricyclic framework of eunicin. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: Allene; Carbohydrate; cembranoid; eunicin; Ring closing metathesis

First iodocyclization reaction of allene-thioureas: an efficient approach to bicyclic beta-lactams - Garud, Dinesh R.; Jadhav, Amol R.; Lahore, Santosh V.; Kahar, Nilesh M.; Joshi, Rohini R.; Joshi, Ramesh A.; Koketsu, Mamoru (Tetrahedron Letters, 2014)
The regioselective iodocyclization reaction of allene-thioureas is described, for the first time, for the synthesis of bicyclic beta-lactams. The substitution at the allenyl part heavily influenced the iodocyclization reaction. The iodocyclization reaction of the unsubstituted allene-thioureas afforded six-membered 3-thia-1-dethiacephems whereas, the substituted allene-thiourea afforded seven-membered thiazepines along with five-membered isopenams. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Allene; beta-Lactams; Iodocyclization; Regioselective; thiourea